Outcomes of a GnRH Agonist Trigger Following a GnRH Antagonist or Flexible Progestin-Primed Ovarian Stimulation Cycle - Kalafat, Erkan; Turkgeldi, Engin; Yıldız, Sule; Dizdar, Merve; Keles, Ipek; Ata, Baris (Frontiers in Endocrinology, 2022)
A suggested explanation for pituitary suppressive effects of progestin primed oocyte stimulation cycles (PPOS) is pituitary luteinizing hormone (LH) depletion with progestin exposure during the follicular phase. GnRH agonist (GnRHa) trigger releases endogenous LH from the pituitary and if LH depletion theory is correct, the response to agonist trigger would be dampened in PPOS cycles. In this study, we compared the performance of GnRHa trigger after PPOS and GnRH antagonist ovarian stimulation cycles. All women who underwent ovarian stimulation with GnRH antagonist or fPPOS and received a GnRH agonist trigger were eligible for inclusion. Outcomes included number of metaphase-II (MII) oocyte retrieved per cycle, rates of empty follicle syndrome, maturation, fertilization, blastulation, and cumulative clinical pregnancy per stimulation cycle. During the screening period, there were 166 antagonist and 58 fPPOS cycles triggered with a GnRH agonist. Groups were matched for potential confounders using propensity score matching. Progestin downregulated cycles had 19% high mature oocyte yield (median: 14 vs 19 MII oocytes, P=0.03). Cumulative ongoing pregnancy or live birth rates were estimated after matching for transferred embryo count, and rates were similar between GnRH antagonist and flexible PPOS group (57.0% vs 62.1%, P =0.68). However, the number of remaining blastocysts was higher in the flexible PPOS group (median: 5.0 vs 6.0, P <0.001). LH levels were higher in flexible PPOS cycles compared to GnRH antagonist cycles up to trigger day (P < 0.001). After the agonist trigger, PPOS cycles were associated with a steeper luteinizing hormone surge compared with antagonist cycles (P = 0.02). Higher endogenous gonadotropin levels through the stimulation period and an LH surge of higher magnitude following a GnRH agonist trigger suggest a milder pituitary suppression by fPPOS, which needs to be confirmed in larger samples. It appears that progestins do not deplete pituitary LH reserves and a GnRH agonist trigger is usable after PPOS in women with high ovarian reserve.